2012
DOI: 10.1007/s00268-012-1497-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Caudate Lobectomy in Type IIIA and IIIB Hilar Cholangiocarcinoma: A 15‐year Experience in a Tertiary Institution

Abstract: Caudate lobectomy contributed to improvement of DFS and OS in type III hilar cholangiocarcinoma. Other prognostic factors include positive LN metastasis and presence of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 48 publications
1
46
0
1
Order By: Relevance
“…Japanese high volume centers in which combined caudate lobe resection is routinely performed report relatively high curative resection rate (59-87%) and 5 year survival rate (33-44%) [74,87,124,127,[142][143][144][145][146][147][148]. Several reports from other countries also showed the benefits of this procedure for hilar/upper bile duct carcinoma [149][150][151][152][153][154]. These results indicate that combined caudate lobe resection should be performed in most cases of hilar or upper bile duct carcinoma for increasing curative resection rate and better prognosis.…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 85%
“…Japanese high volume centers in which combined caudate lobe resection is routinely performed report relatively high curative resection rate (59-87%) and 5 year survival rate (33-44%) [74,87,124,127,[142][143][144][145][146][147][148]. Several reports from other countries also showed the benefits of this procedure for hilar/upper bile duct carcinoma [149][150][151][152][153][154]. These results indicate that combined caudate lobe resection should be performed in most cases of hilar or upper bile duct carcinoma for increasing curative resection rate and better prognosis.…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 85%
“…Local resection in combination with caudate lobectomy for hilar CCA has resulted in a greater number of patients with R0 resection and has improved the longterm prognosis. 58 More aggressive resection with trisegmentectomy or even semihepatectomy has been used in some patients and was associated with significantly increased survival. [59][60] However, the postoperative mortality due to liver dysfunction is also slightly higher with these more extensive operations.…”
Section: -57mentioning
confidence: 99%
“…[59][60] However, the postoperative mortality due to liver dysfunction is also slightly higher with these more extensive operations. [58][59][60][61] To reduce the risk of postoperative liver dysfunction with semihepatectomy or resection of more than 50-60% of the liver, some researchers have employed preoperative ipsilateral portal vein embolization, which can induce compensatory hypertrophy of the future remnant liver.…”
Section: -57mentioning
confidence: 99%
“…Overall 3986 patients with a median age of 66 (range 58-70) were described and 2128 patients (53%) suffered from perihilar cholangiocarcinoma ( Table 1). [12][13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In addition, 11 studies reporting exclusively perihilar The median number of lymph node count was reported in all 20 studies ranging from 2-24 lymph nodes (Fig 2). In 60% of the studies (n=12) exclusively regional lymphadenectomy was described.…”
Section: Descriptive Cohortmentioning
confidence: 91%